Designing for Psychological Change: Individuals' Reward and Cost Valuations in Weight Management - Hsu, Anne; Blandford, Ann (JMIR Publications, 2014)
BackgroundKnowledge of the psychological constructs that underlie behavior offers valuable design opportunities for persuasive systems. We use the decision theory, which describes how behavior is underpinned by reward-cost valuations, as a framework for investigating such psychological constructs to deliver design objectives for weight management technologies. ObjectiveWe applied a decision theory-based analysis in the domain of weight management to understand the rewards and costs that surround individuals' weight management behaviors, with the aim of uncovering design opportunities for weight management technologies. MethodsWe conducted qualitative interviews with 15 participants who were or had been trying to lose weight. Thematic analysis was used to extract themes that covered the rewards and costs surrounding weight management behaviors. We supplemented our qualitative study with a quantitative survey of 100 respondents investigating the extent to which they agreed with statements reflecting themes from the qualitative study. ResultsThe primary obstacles to weight management were the rewards associated with unhealthy choices, such as the pleasures of unhealthy foods and unrestricted consumption in social situations, and the significant efforts required to change habits, plan, and exercise. Psychological constructs that supported positive weight management included feeling good after making healthy choices, being good to oneself, experiencing healthy yet still delicious foods, and receiving social support and encouraging messages (although opinions about encouraging messages was mixed). ConclusionsA rewards-costs driven enquiry revealed a wide range of psychological constructs that contribute to discouraging and supporting weight management. The constructs extracted from our qualitative study were verified by our quantitative survey, in which the majority of respondents also reported similar thoughts and feelings. This understanding of the rewards and costs surrounding weight management offers a range of new opportunities for the design of weight management technologies that enhance the encouraging factors and alleviate the discouraging ones.